Cellulase Enzyme Production Using Solid State Fermentation Method From Waste – A Review - Maftukhah, Siti (UNISTEK, 2019)
Solid fermentation (SSF) has built credibility in recent years in the biotechnology industry because its application has the potential to produce biologically active secondary metabolites, in addition to animal feed, fuel, food, industrial chemicals and pharmaceutical products, it has also emerged as an alternative interesting method that replaces the submerged fermentation method(SmF). This paper reviews the meaning of SSF, the factors that influence the success of SSF, the advantages and disadvantages of SSF, the meaning of cellulase enzymes, the use of cellulase enzymes and the production of cellulase enzymes using SSF from waste. The waste consists of agricultural waste and food processing waste with various microorganisms, optimization and pretreatment. So that the various levels of enzyme activity produced depend on the type of waste.